Exploring Digital Storytelling Strategies through Live Streaming as an Inclusive Promotional Medium for Disability-Owned MSMEs: A Case Study of Tiara Handycraft - Putri, Lily Harlina (LP2M IAIN Palopo, 2026)
Digital transformation creates new opportunities for micro, small, and medium enterprises (MSMEs) to expand their market reach; however, it also presents challenges related to digital inclusion, particularly for businesses that serve persons with disabilities. This study aims to analyze the implementation of storytelling-based marketing through live streaming as an inclusive digital marketing strategy at Tiara Handycraft, a patchwork handicraft MSME that empowers persons with disabilities. Using a qualitative case study design, data were collected through in-depth interviews, observations of live-streaming activities, and social media documentation. The data were then analyzed using thematic analysis techniques. The research findings indicate that storytelling that emphasizes social narratives and sustainability values is a key driver of digital promotion, effectively fostering emotional engagement among consumers. Furthermore, live streaming serves as an interactive medium that enables the active participation of persons with disabilities in marketing activities, thereby strengthening digital inclusion and enhancing the social legitimacy of MSMEs. Integrating storytelling, live streaming, and social entrepreneurship values contributes to the development of an empathetic brand image oriented toward social impact. This research contributes theoretically by extending the body of knowledge on digital marketing and social entrepreneurship through the lens of digital inclusion. From a practical perspective, the findings provide a reference for social MSMEs in designing digital marketing strategies that prioritize not only economic gains but also empowerment and social values